A qualitative study of the barriers to prehospital management of acute pain in children. Issue 6 (21st March 2013) - Murphy, Adrian; Barrett, Michael; Cronin, John; McCoy, Siobhan; Larkin, Philip; Brenner, Maria; Wakai, Abel; O'Sullivan, Ronan
Abstract : Introduction: Effective pain management in the prehospital setting is gaining momentum as a potential key performance indicator by many emergency medical service systems, but historically has been shown to be inadequate, particularly in the paediatric population. This study aimed to identify the barriers, as perceived by a national cohort of advanced paramedics (APs), to achieving optimal prehospital management of acute pain in children. Methods: A qualitative approach was employed to capture data through two focus group interviews. Sixteen APs were invited to participate in this study. Both focus groups were audio recorded, transcribed and analysed using Attride–Stirling's framework for thematic network analysis. Results: The global theme 'Understanding Barriers to the Prehospital Management of Acute Pain in Children' emerged from three organising themes as follows: AP education and training; current clinical practice guidelines for paediatric pain management; realities of prehospital practice. Limited exposure to children in the prehospital setting, difficulty assessing pain intensity in small children, and challenges in administering oral or inhaled analgesic agents to distressed and uncooperative children were highlighted by participants. Short transfer times to the emergency department, and a 'medical' cause of pain were also implicated as examples of when children are less likely to receive analgesia from practitioners. Conclusions: The pathway to improving care must include an emphasis on improvements in practitioner education and training, offering alternatives to assessing pain in preverbal children, exploring the intranasal route of drug delivery in managing acute severe pain, and robustly developed evidence-based guidelines that are practitioner friendly and patient-focused.